The role of bending stress on the initiation of reverse transverse defects. (January 2021) - Mojumder, Soumyajit; Su, Hang; Qiu, Cong; Mutton, Peter; Singh, Aparna; Yan, Wenyi
This paper investigated the role of longitudinal reverse bending stress on the initiation of reverse transverse defects. The longitudinal reverse bending stress occurs due to the reverse bending of the rail between two-wheel passage leading to the generation of tensile bending stress at the railhead and the lower head areas. The longitudinal bending stress was investigated as part of a parametric study on the rail cant angle, rail stiffness, lateral-to-vertical load ratio, and rail profile. A finite element model was created by using ABAQUS to analyze the extent of reverse bending in rails with respect to the chosen set of parameters. Under different lateral-to-vertical load ratios of 0, 0.3, 0.5, and 0.7, the maximum stress at the rail lower gauge corner was found to vary between 14.57MPa and 15.47MPa under the reverse bending condition. Similarly, low values of tensile stress under the reverse bending scenario were observed with changes in the rail cant angle and axle spacing with respect to different coal and iron ore wagons. The results revealed that the magnitude of the bending stress under different conditions of reverse bending was not significant enough to initiate a crack at the lower gauge corner.